2015
DOI: 10.1152/jn.00046.2015
|View full text |Cite
|
Sign up to set email alerts
|

Brief anesthesia, but not voluntary locomotion, significantly alters cortical temperature

Abstract: Changes in brain temperature can alter electrical properties of neurons and cause changes in behavior. However, it is not well understood how behaviors, like locomotion, or experimental manipulations, like anesthesia, alter brain temperature. We implanted thermocouples in sensorimotor cortex of mice to understand how cortical temperature was affected by locomotion, as well as by brief and prolonged anesthesia. Voluntary locomotion induced small (∼ 0.1 °C) but reliable increases in cortical temperature that cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 64 publications
8
43
0
Order By: Relevance
“…The temperature was 36.8°C 30 min after recovery from anesthesia (N ϭ 2 mice), consistent with previous reports (Shirey et al 2015).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The temperature was 36.8°C 30 min after recovery from anesthesia (N ϭ 2 mice), consistent with previous reports (Shirey et al 2015).…”
Section: Resultssupporting
confidence: 91%
“…Brain temperature 500 m below the cranial window was 35.3°C in awake head-fixed mice in the absence of objective immersion, which reduced to 34.3°C with room temperature immersion water placed above the window and a microscope objective immersed (N ϭ 2 mice). Anesthesia induces prolonged brain cooling for up to 30 min after recovery (Shirey et al 2015). We found that 1.25% isoflurane anesthesia reduced brain temperature 500 m below the dura to 33.8°C and 34.4°C in the presence and absence of immersion water, respectively, while core temperature was maintained at 37°C (N ϭ 2 mice).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…During the experimental setup, the rat was briefly anesthetized by isoflurane (2%) to secure the head and body in a restraining system with a built-in coil. Isoflurane was discontinued immediately after each rat was restrained, and sufficient time was given so that all rats were fully awake during imaging sessions (Shirey et al 2015). Body temperature was maintained at 37 °C by a feedback controlled heating pad while the rats were imaged.…”
Section: Methodsmentioning
confidence: 99%
“…This concentration induces a deep anesthetic plane, characterized by loss of withdrawal reflexes, as well as a significant decrease in thalamic and cortical activity (Detsch et al 1999; 2002; Shirey et al 2015). Furthermore, 1.5–2% isoflurane produces an anesthetic state in which the electrocorticogram signal is dominated by a 1–2 Hz signal in the power spectrum, which is consistent with a loss of consciousness (Friedburg et al 1999; Smith et al 2012a; Alloway et al 2014).…”
Section: Methodsmentioning
confidence: 99%